2012
DOI: 10.3109/00016489.2012.691211
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the various classifications for parapharyngeal space involvement in nasopharyngeal carcinoma

Abstract: The incidence of PPS involvement was 81.8%. The 5-year overall survival (OS), progression-free survival (PFS), distant metastasis-free survival (DMFS), and local relapse-free survival rates (LRFS) of the patients with and without PPS involvement were 68.1% and 90.2% (p = 0.010), 66.1% and 87.2% (p = 0.013), 76.7% and 93.6% (p = 0.032), and 84.9% and 93.1% (p = 0.220), respectively. Multivariate analysis showed that PPS involvement (yes vs no) was not an independent prognostic factor. However, graded PPS involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In previous studies, primary tumor volume and invasion of the parapharyngeal space were found to be closely related to NPC survival rates [10], [11], [12]. Thus, tumor volume and parapharyngeal space invasion may represent prognostic factors that could be incorporated into the existing TNM system based on the accessibility of US for tumor detection [13], [14]. However, additional studies will be needed to further evaluate this possibility.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, primary tumor volume and invasion of the parapharyngeal space were found to be closely related to NPC survival rates [10], [11], [12]. Thus, tumor volume and parapharyngeal space invasion may represent prognostic factors that could be incorporated into the existing TNM system based on the accessibility of US for tumor detection [13], [14]. However, additional studies will be needed to further evaluate this possibility.…”
Section: Discussionmentioning
confidence: 96%
“…Parapharyngeal tumor involvement, especially in the carotid area, is a stronger predictor for poor prognosis [15,16]. Even after the introduction of faciocervical fields, the prognostic value of parapharyngeal involvement remained varied in different studies, mainly because the boost in the parapharyngeal area was not adopted in all the institutions [17][18][19][20][21]. However, with the prevailing use of MRI, CT simulation, and 3D-CRT or IMRT, the possibility of inadequate dose in this area was reduced, and parapharyngeal space extension per se no longer predicts disease outcome [5,22,23].…”
Section: Mri Was Considered As the Preferred Imaging Modality For Npcmentioning
confidence: 99%
“…It is generally accepted that NPC has a better prognosis with radiotherapy as the first-line therapy, but has reached a plateau at the indicated doses [5,6]. Consequently, there is an urgent need to develop novel radiosensitizers to achieve better curative effect, without increasing radiation injury.…”
Section: Introductionmentioning
confidence: 99%